Determinants of Value Perception on Purchase Decisions for Laboratory Instrumentation Products in the COVID-19 Pandemic Era - Santi Atsiriani; Nandan Limakrisna; Agus Setyo Pranowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this study is to determine the influence of digital communication and after-sales service on purchasing decisions, with perceived value as an intervening variable. The data in this study were obtained from 166 respondents who use moisture analyzer instruments, with the respondents coming from Quality Control, Quality Assurance, and Research and Development departments. Data analysis in this study used SPSS 26.0. The results of the study indicate that digital communication and after-sales service significantly influence perceived value. However, neither has a direct impact on purchase decisions. Perceived value does not mediate the influence of digital communication, but it does mediate the influence of after-sales service on purchase decisions. After-sales service plays a crucial role in improving purchasing decisions thru value perception in the B2B sector, especially during the pandemic. This research can provide practical input for the development of marketing strategies in the laboratory instrument industry in Indonesia.